1044. The Incidence and Severity of Drug interactions Before and After Switching Antiretroviral Therapy to Bictegravir/Emtricitabine/Tenofovir Alafenamide in Treatment Experienced Patients. (31st December 2020) - Schafer, Jason J; Pandit, Neha S; Cha, Agnes; Huesgen, Emily; Badowski, Melissa E; Sherman, Elizabeth; Cocohoba, Jennifer; Shimada, Ayako; Keith, Scott
Abstract: Background: Switching antiretroviral therapy (ART) in virally suppressed people with HIV (PWH) can simplify treatment, improve tolerability, and limit long-term toxicity. It can also influence the presence of drug interactions (DIs) in a positive or negative manner among patients receiving concomitant medications (CMs). The extent to which switching ART to bictegravir/emtricitabine/tenofovir alafenamide (BIC/FTC/TAF) influences DIs in treatment-experienced PWH is unclear. The purpose of this study was to assess changes in the incidence and severity of DIs after switching to BIC/FTC/TAF. Methods: This was a multicenter retrospective cohort study of PWH on ART and at least one prescription CM who switched to BIC/FTC/TAF between 3/2018 and 6/2019. Using the University of Liverpool's HIV drug interaction checker, two DI analyses were performed for each patient. The first assessed patients' pre-switch ART regimen with their CM list. The second assessed the same CM list with BIC/FTC/TAF. Each ART-CM combination was given a numerical score of 0 (no or potential weak interaction), 1 (potential interaction), or 2 (contraindicated interaction). Total DI scores for each patient, both before and after switching to BIC/FTC/TAF, were then calculated. A paired t-test analyzed changes in DI scores following ART switches and a linear regression model examined factors contributing to DI score reductions. Results: A total of 411 patients were included in the analysis (Table 1) of which 236 (57%) had at least one DI present at baseline. On average, patients had a baseline DI score of 1.4 (SD 1.8) and experienced a 1 point reduction (95% CI -1.1, -0.8) after switching to BIC/FTC/TAF (p < 0.0001). After adjusting for demographic variables as well as baseline ART and CM categories in the regression model, switching to BIC/FTC/TAF led to significant DI score reductions in patients receiving CMs for the following conditions: cardiovascular disease, neurologic and psychiatric disorders, chronic pain, inflammation, gastrointestinal and urologic conditions and conditions requiring hormonal therapy (Table 2). Table 1. Descriptive Summary of Baseline Characteristics, n =411. Table 2. Linear Regression for the Difference of DI scores (post – pre), n =376. Conclusion: Switching ART to BIC/FTC/TAF can reduce the incidence of DIs among treatment-experienced PWH who are receiving CMs for a broad range of comorbid conditions. Disclosures: Jason J. Schafer, PharmD, MPH, Gilead (Research Grant or Support)Merck (Grant/Research Support, Advisor or Review Panel member)ViiV (Advisor or Review Panel member) Elizabeth Sherman, PharmD, Gilead (Grant/Research Support) Jennifer Cocohoba, PharmD, AAHIVP, BCPS, Viiv (Grant/Research Support)